2012
DOI: 10.5140/jass.2012.29.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Observations of Eccentric Accretion in Algol-type Binary Stars

Abstract: Some Algol-type interacting binary stars exhibit strange photometric variations that can be phase-dependent and/or secular. This paper discusses the possibility of explaining these observed variations as resulting from an accretion structure eclipsing one or both of the stars. Some previous studies are reviewed and suggestions for future work are made, including the prospective of incorporating data from the Kepler Observatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Although the errors of the phenomenological parameters are not very large (up to few percent), there may be systematic errors up to a dozen percent due to the simplicity of the model. These estimates may be used as preliminary values for further modeling using extended physical models based on the Wilson & Devinney (1971) code and it's extensions (Wilson 1979(Wilson , 1994(Wilson , 2012(Wilson , 2014Zola et al 1997Zola et al , 2010Bradstreet 2005;Kallrath et al, 2009;Linnel 2012;Reed 2012;Rucinski 2010;Prsa et al 2012). Such study of eclipsing binaries with the CBNU observations are reported by Jeong & Kim (2013); Kim & Jeong(2012); Jeong & Kim (2011) and Kim et al (2010a).…”
Section: Discussionmentioning
confidence: 94%
“…Although the errors of the phenomenological parameters are not very large (up to few percent), there may be systematic errors up to a dozen percent due to the simplicity of the model. These estimates may be used as preliminary values for further modeling using extended physical models based on the Wilson & Devinney (1971) code and it's extensions (Wilson 1979(Wilson , 1994(Wilson , 2012(Wilson , 2014Zola et al 1997Zola et al , 2010Bradstreet 2005;Kallrath et al, 2009;Linnel 2012;Reed 2012;Rucinski 2010;Prsa et al 2012). Such study of eclipsing binaries with the CBNU observations are reported by Jeong & Kim (2013); Kim & Jeong(2012); Jeong & Kim (2011) and Kim et al (2010a).…”
Section: Discussionmentioning
confidence: 94%